Green Open Space Priority Modelling Using GIS Analysis in West Jakarta - Prama Ardha Aryaguna; Ghefra Rizkan Gaffara; Dayu Ariesta Kirana Sari; Ade Arianto (Faculty of Geography, Universitas Gadjah Mada, 2022)
Green open space is one of the most important land uses, especially in densely populated urban areas. Public Green Open Land in each area regulated in Law No. 1 of 2007 is at least 20%. Based on data from the Department of Creative Works, Land and Spatial Planning as well as the Environment Agency of DKI Jakarta, West Jakarta's Green open space asset area is 277.45 Ha of the total area of West Jakarta, which is 12543 Ha. There is a need for a study to determine the potential land for green open space in West Jakarta to catch up on the fulfillment of public green open space based on spatial and regional analysis. One of the GIS-based methods that can be used to determine potential green open space is the decision tree method. This method uses AHP analysis in its formulation based on experts in the relevant agencies. In total there are 8 parameters that influence in determining potential green open space in West Jakarta, namely flood risk, air quality, population, distance to roads, distance to water sources, building density and distance to green open space assets. The modeling results are divided into five classes ranging from very priority to not priority. The total area of land that is much prioritized to be used as green open space is 95.57 hectares spread out. The modeling results show that there are still potential lands to be used as green open spaces in West Jakarta.